2021
DOI: 10.1126/sciadv.abi6802
|View full text |Cite
|
Sign up to set email alerts
|

TREM-2 is a sensor and activator of T cell response in SARS-CoV-2 infection

Abstract: TREM-2 recognizes SARS-CoV-2 membrane protein and activates CD3ζ/ZAP70/STAT1 signal pathway to induce antiviral T H 1 response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 74 publications
(118 reference statements)
1
17
0
Order By: Relevance
“…Hence TREM-2 may be involved in lung localised CD4 + T cells in COVID-19 patients. TREM-2 expression on both CD4 + and CD8 + T cells was correlated to TCR dependent markers including CD134 (OX-40), CD137, CD69 and CD25 (197). This implies that TREM-2 plays critical role in T cell activation and differentiation in SARS-CoV-2 pneumonia.…”
Section: Local Immune Response In Covid-19 Pneumoniamentioning
confidence: 84%
See 1 more Smart Citation
“…Hence TREM-2 may be involved in lung localised CD4 + T cells in COVID-19 patients. TREM-2 expression on both CD4 + and CD8 + T cells was correlated to TCR dependent markers including CD134 (OX-40), CD137, CD69 and CD25 (197). This implies that TREM-2 plays critical role in T cell activation and differentiation in SARS-CoV-2 pneumonia.…”
Section: Local Immune Response In Covid-19 Pneumoniamentioning
confidence: 84%
“…In severe COVID-19 disease the soluble mediators IL6, IL1b, CXCL8 and CXCL10 are expressed in a TREM-2 dependent manner by macrophages (196). Other studies have demonstrated that TREM-2 is constitutively expressed on T cells during SARS-CoV-2 infection leading to rise in IL-2, IFN-g, IL-1B and IL-4 thereby being a key mediator in T cell immunity and inflammation (197). TREM-2 expression was higher in peripheral blood and lung infiltrating CD4 + and CD8 + T cells of severe and non-severe COVID 19 patients than healthy donors.…”
Section: Local Immune Response In Covid-19 Pneumoniamentioning
confidence: 99%
“…A modified distribution of the ZAP70 kinase on the plasma membrane of T-cells contributes to the signal transduction and amplification of the TCR [84] . Interestingly, CD3/ZAP70 protein has been shown to interact with TREM-2 in the T-cells of patients infected with SARS-CoV-2 [85] .…”
Section: Discussionmentioning
confidence: 99%
“…A modified distribution of the ZAP70 kinase on the plasma membrane of T-cells contributes to the signal transduction and amplification of the TCR [48]. Interestingly, CD3/ZAP70 protein has been shown to interact with TREM-2 in the T-cells of patients infected with SARS-CoV-2 [49]. The ASPH and C5orf30 genes, which were identified as significant DEGs in our study, have been identified previously as markers of severe infection [50].…”
Section: Discussionmentioning
confidence: 99%